2015
DOI: 10.12928/telkomnika.v13i1.924
|View full text |Cite
|
Sign up to set email alerts
|

Raptor Code for Energy-Efficient Wireless Body Area Network Data Transmission

Abstract: IntroductionWireless Body Area Network (WBAN) is a cluster of wireless sensors worn by humans mainly for the purpose of medical condition monitoring. The human physiological data such as blood pressure or body temperature are monitored by the sensors and sent to a data processor regardless of the location or the activity of the subject [1]. WBAN is a structure which contains a short-range communication system based on IEEE 802.15.6. The standard allows for lowpower and small-sized devices and includes characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The raptor code showed greater efficiency over uncoded FSK and LDPC coded link [ 14 ]. The comparison result of raptor code and bose-chaudhuri-hocquenghem (BCH) code in a fading environment showed that the BCH coded data achieves higher energy efficiency for a link length of 10 m or less [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The raptor code showed greater efficiency over uncoded FSK and LDPC coded link [ 14 ]. The comparison result of raptor code and bose-chaudhuri-hocquenghem (BCH) code in a fading environment showed that the BCH coded data achieves higher energy efficiency for a link length of 10 m or less [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The research results of noise immunity signals of frequency shift keying indicate that the best features has the coherent reception of FSK signals . Thus, at the BER level of 10-5 the energy gain of MSK (coherent acceptance) before DQPSK is 1.5 dB, and before non -coherent reception -4 dB [9], [11][12][13].…”
Section: Resultsmentioning
confidence: 99%
“…Each of the hypotheses, which is remained for the next measure is complemented by zero and one, and two new hypotheses are being formed. The reference signals 1 Xr U and 2 Xr U are generated for each hypothesis to implement the formula (12). As the initial value, the last k-th bit estimate isn't used and the bit offset to the depth of the given scenario, i.e. )…”
Section: The Methods Of Optimization Of the Device Signal Processingmentioning
confidence: 99%
“…In recent years lot of research has been done to enhance the quality of received image after transmission in noisy channel, this problem can be solved using different techniques (source coding, channel coding , joint source channel coding or by optimize in restoration filters) as shown in articles [1][2][3].…”
Section: Introductionmentioning
confidence: 99%